Factors Influencing Pregnant Women's Use of Patient Decision Aids and Decision Making on Prenatal Screening: A Qualitative Study - Razieh Zahedi; Leila Nemati-Anaraki; Shahram Sedghi; Mamak Shariat (Tehran University of Medical Sciences, 2021)
Objective: We aimed to identify factors influencing pregnant women's use of patient decision aids (PtDA) and decision making on prenatal screening. Materials and methods: This qualitative study was conducted between July 2019 and June 2020 in Tehran, Iran. The sample included 26 pregnant women selected by purposive sampling. The participants used a prenatal screening PtDA, then interviewed about factors that would influence their decision making and use of decision aids. The data were analyzed by conventional content analysis. Results: Three categories were identified for the process of and factors influencing decision making, including the current decision making process, expected decision making process, and factors influencing decision making. Also, five categories were identified as factors affecting the use of PtDAs, including the content of decision aids, the appearance of decision aids, the decision aid platform, the provision of decision aids, and the sub features of decision aids. Conclusion: To design, develop, and implementation of PtDAs for pregnant women, one should identify the factors affecting pregnant women's decision making and the use of decision aids. This study helped to the identification of these factors, which is the first step towards the use of PtDAs by pregnant women and their participation in decision making.